Academic Procrastination in University Students: Factorial Analysis of its Dimensions and a Self-Regulation-Based Intervention - Barradas-Arenas, U.D.; Vazquez-Aragón, M.R.; Pérez-Cruz, J.A.; Cocón-Juárez, J.F.; Juárez-de la Cruz, G. (RIIIT Revista Internacional de Investigación e Innovación Tecnológica, 2026)
This study addresses academic procrastination among students at the Universidad Autónoma del Carmen, México, a phenomenon that negatively affects academic performance and student well-being. In a quantitative, correlational, cross-sectional study using factor analysis, four dimensions associated with procrastination were identified: goals and priorities, management elements, disorganization, and control. The results highlight the importance of self-regulation, planning, and organizational skills as key components for understanding academic procrastination behaviors and guiding support strategies.Based on these findings, the mobile application “Hazloo” was designed and developed as a digital support tool for task and time management, aligned with the identified dimensions. Usability testing yielded positive ratings for ease of use and activity organization, while also identifying areas for improvement related to visual design and error prevention. In conclusion, this study provides evidence on the dimensional structure of academic procrastination and presents the design of a technological solution intended to support self-regulation and the organization of academic work; future research should evaluate its effectiveness using pretest–posttest designs and comparison groups.
Keywords: Higher education; Time management; Self-regulation; Academic procrastination; Mobile application.